Scandinavian legends and folk-tales - Jones, Gwyn; Kiddell-Monroe, Joan (New York; London: Oxford unversity press., 1966)
Twenty-four tales from the folklore of Denmark, Norway, Iceland, and Finland.
includes index
Keywords: Tales -- Scandinavia; Legends -- Scandinavia; Fairy tales -- Scandinavia; Folklore -- Scandinavia; Fairy tales